Study on the fretting wear behavior over a wide temperature range of an Inconel 718 superalloy deposited by laser cladding. (January 2023) - Xu, Zhibiao; Li, Dexiang; Lu, Zhijie; Lv, Xiaowen; Liu, Yecheng; Liu, Jihua; He, Chenggang
Highlights: The fretting wear mechanisms of Inconel 718 alloys deposited by laser cladding in different temperature were analyzed. In PSR, the wear damage mainly shows elastic–plastic deformation, fatigue wear and abrasive wear. In MFR and GSR, the wear damage was mainl combined with fatigue wear, peeling, adhesive wear and oxidative wear. High temperatures induces oxidation reactions during friction and slow down the wear of the material. Abstract: Fretting tests were performed on an Inconel 718 superalloy against GCr15 steel in a range of 25 ℃ < T < 400 ℃ to investigate the wear mechanism of the laser cladding-deposited Inconel 718 superalloy over a wide temperature range. The results show that when the displacement amplitude was 15 μm, the fretting was running in a partial slip regime (PSR), and the wear damage mainly showed elastic–plastic deformation, fatigue wear and abrasive wear. When the displacement amplitude increased to 100 μm, fretting occurred in a mixed slip regime (MSR) and gross slip regime (GSR). With continuous fretting wear, the dissipated energy of the material decreased gradually with increasing temperature in a stable state. The wear damage was mainly combined with fatigue wear and peeling. When the temperature was 100 ℃, the coefficient of friction (COF) value in the stable state was large. As the temperature increased, adhesive wear and oxidative wear gradually predominated in the fretting tests. The effect of high temperature easily formed an adhesive layer on the worn surface with wear reduction, especially at a high displacement amplitude.